GEOPHYSICAL-STRUCTURAL FRAMEWORK IN A MINERALIZED REGION OF NORTH WESTERNMOST CAMAQUA BASIN, SOUTHERN BRAZIL - Pereira, Henrique Garcia; Fonseca Ferreira, Francisco Jose; Moreira, Cesar Augusto [UNESP]; Ferreira da Silva, Vinicius Antunes (Inst Geophysics Unam, 2021)
Airborne and ground magnetic and gravimetric maps provide important information about the spatial distribution of causative sources in the geological substrate. These sources normally have different physical properties and geometric shapes and are located at different depths, making it difficult to identify the geological features that correspond to the sources. Filtering and enhancement techniques can be used to highlight features in potential field anomalies (such as center and edges of sources). Also, these techniques remove associated noise, isolate shallow from deep sources, and estimate depths. We applied enhancement and depth estimation techniques in airborne and ground potential field data to delineate a subsurface structural framework of two copper occurrences (Victor Teixeira and Capao Grande) in the northwestern border of Camaqua Basin with the Sul-Riograndense Shield. Our results confirmed previously recognized structures and revealed an interconnected structural framework, which has an estimated depth of 170 m by Euler solutions. This configuration suggests a possible connection between the two mineralization outcrops, which are separated by a distance of 2,300 m.
Keywords: Magnetometry; Gravimetry; Lineaments; Sul-Riograndense Shield; Cupriferous Mineralizations